A palhaçaria como caminho de ensino e aprendizagem para sala de aula - SARMENTO FILHO, Rubervaldo Cruz (2023)
The present work aims to analyze 4 clowning games/exercises that I consider extremely important for my artistic training, as well as their possible uses in the classroom. Understanding and cataloging the personal experiences that I obtained in my artistic work from 2014 to 2022, I come to address the spaces and trainers that I had the opportunity to meet throughout this process, as well as their influences for my research on the discovery of the Clown and their actions in the classroom. Taking into account my training and the spaces where I occupied, I continue with the cataloging of these experiences. This research intends to become a possible way to bring understanding to other artists, who have also gone through a similar experience of building a framework of theatrical games/exercises that can be used by other educators.